Preparation of Superhydrophobic Polypropylene Membrane Using Dip-Coating Method: The Effects of Solution and Process Parameters. Issue 2 (22nd January 2017) - Himma, Nurul Faiqotul; Wardani, Anita Kusuma; Wenten, I Gede
ABSTRACT: Superhydrophobic polypropylene hollow fiber membranes were prepared through two-step dip-coating process. The effects of solution and process parameters were investigated. It was found that polymer solution concentration and temperature were crucial parameters to obtain homogeneous coating. High hydrophobicity could be achieved by controlling the polymer solution concentration and drying temperature. Using methyl ethyl ketone as nonsolvent, the membrane surface roughness was increased, resulting in superhydrophobicity with high contact angle of 151.3°. The modified membrane still exhibited lower flux than unmodified membrane in water–oil separation due to porosity decrease. However, their water rejections were comparable. GRAPHICAL ABSTRACT: